Analisis Semiotika terhadap Nilai-Nilai Kesetiaan dalam Lirik Lagu Nidji - Reika Eugenia Astriani (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
This study aims to uncover the meaning of loyalty and sacrifice in the lyrics of the song "Sumpah dan Cinta Matiku" by Nidji through Roland Barthes' semiotic approach. The analysis is conducted at three levels of meaning, namely denotative, connotative, and myth, to understand how song lyrics form emotional messages as well as ideologies in Indonesian popular culture. At the denotative level, a literal meaning is found regarding the pledge of loyalty and commitment of love between two people who are emotionally bound to each other. The connotative level displays emotional and cultural meanings in the form of a willingness to sacrifice and steadfastness in maintaining love, which is often depicted as a heroic and struggle-filled act. Meanwhile, at the mythical level, this song brings up the ideology of romantic love that is absolute, eternal, and demands unconditional sacrifice, as often found in love narratives in other popular media. Lyrics such as "Sumpah mati hanya kau yang kucinta" and "Meski badanku has become one with the ground, cintaku tetap hidup bagi bagi" reflect the cultural construction that true love must be proven by suffering, extreme loyalty, and even sacrifice of life. This meaning emphasizes that love is not merely an emotional connection, but a form of total devotion that cannot be shaken by any circumstances. This song indirectly instills the idea that love means being willing to lose everything, including one's life, to maintain that love. The results of this study indicate that these songs not only convey personal messages of love but also play a role in shaping and perpetuating the myth of love in society. This finding is reinforced by various previous studies that state that popular music plays a role as a medium for reproducing cultural values, particularly regarding idealized, sacrificial, and irrational love.